Quality Analysis of the Ahmad Dahlan University Digital Library Using the WebQual 4.0 and Importance Analysis Performance (IPA) Method. - Tarmuji, Ali; Akbardillah, K Moch Reza Dwi (Jurusan Informatika, 2023)
Purpose: This paper is the result of research which aims to obtain results of measuring the quality of web services from the Library Unit at Ahmad Dahlan University, especially from the perceptions of student users in order to prepare recommendations for improving services. This paper is the result of research which aims to obtain results of measuring the quality of web services, especially from perceptions student users in order to prepare recommendations for improving service mediaDesign/methodology/approach: Based on sampling data collected using a questionnaire and calculated using statistics. The next step is to measure the WebQuel 4.0 method, the results of which are combined with the Importance Performance Analysis (IPA) method to determine recommendations.Findings/result: The research results show that each independent variable, namely the usability variable and the information quality variable, partially has a relationship or is correlated with the dependent variable, namely user satisfaction, while the interaction service quality variable partially has no relationship or is uncorrelated with the dependent variable. The results of simultaneous hypothesis testing show that the independent variable has an effect on the dependent variable so that the hypothesis can be simultaneously accepted. Based on the analysis using the IPA method, there are three things in Quadrant 1 (Top Priority) which are not in accordance with user expectations and need to be improved, namely